2018
DOI: 10.1590/1806-90882018000600002
|View full text |Cite
|
Sign up to set email alerts
|

Financial Analysis of Enrichment Model Using Timber and Non-Timber Products of Secondary Remnants in the Atlantic Forest

Abstract: Socio-economic aspects can limit the expansion of ecological restoration. One alternative to address this question is the development of restoration models that generate income to farmers in addition to the benefits from conservation itself. We designed and implemented the initiative "Sustenta A Mata," a project developed by The Nature Conservancy and supported by the Brazilian Development Bank (BNDES), to generate economic and social benefits for the communities involved. This study aims to analyze the financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Small-scale management of secondary forest in this region has the potential to produce sufficient merchantable timber to become an incentive for land owners to maintain and recover forest on their farms. Enrichment of young regenerating forests with native palm species used for commercial fruit production and timber species generated an economically viable production model over a 30 year period in the Atlantic Forest of southeastern São Paulo, Brazil (Maier et al 2018).…”
Section: Management Of Naturally Regenerated Forests On Former Agricumentioning
confidence: 99%
“…Small-scale management of secondary forest in this region has the potential to produce sufficient merchantable timber to become an incentive for land owners to maintain and recover forest on their farms. Enrichment of young regenerating forests with native palm species used for commercial fruit production and timber species generated an economically viable production model over a 30 year period in the Atlantic Forest of southeastern São Paulo, Brazil (Maier et al 2018).…”
Section: Management Of Naturally Regenerated Forests On Former Agricumentioning
confidence: 99%
“…Within the forest restoration process, there is a great opportunity to foster monetizable native species for NTFP that could contribute to a biodiversity‐based economy. Considering that currently only few examples of an economic utilization of the Atlantic Forest's rich biodiversity exist (Trevisan et al 2015; Maier et al 2018), there are valuable lessons that can be learnt from the Amazon biome. The Amazon has a long history of biodiversity‐based value chains, including rubber ( Hevea brasiliensis ), açaí ( Euterpe oleracea ) and Brazil nut ( Bertholletia excelsa ), among others (Richards 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has forest restoration been studied from a socioeconomic perspective around the world [8,52,[86][87][88]. In California, Elias et al [89] showed that the exploitation of several, highly profitable products from forest restoration is not only possible but can provide financial support for the restoration efforts.…”
Section: Socioeconomic Outcomes Reported In the Studiesmentioning
confidence: 99%